Economic policy uncertainty and the Indian economy - Ghosh, Raktim; Bagchi, Bhaskar (Emerald points., 2023)
As businesses, consumers, and investors make key financial decisions amid Economic Policy Uncertainty (EPU), there is the danger that many might freeze investment projects and hiring, leading to contractions of the economy. These are evident in the Indian economy as a whole and specifically in Indian stock markets indices such as the BSE Sensex and Nifty 50, import and export figures, T-bills, FDI, FPI, and GDP. In this important and timely work, Ghosh and Bagchi examine variables and phenomenon from April 2003 to January 2022, encompassing: * The global financial recession period (December 2007 to June 2009) * The pre-recession period (April 2003 to November 2007) * The post-recession along with pre-COVID-19 period (July 2009 to February 2020) * The COVID-19 period (March 2020 to January 2022) * The Russia-Ukraine Conflict Period (September 2021 to July 2022) This is essential reading for scholars and practitioners dealing with Economic Policy Uncertainty (EPU) in the Indian context, and in macro-economics at large.